Prevalance of hepatitis B and hepatitis C infection in Leprosy patients - Emin ALTIPARMAK; Mukadder KOÇAK; Nihal KUNDAKÇI; Yasemin KOŞAR; Buket PENÇE; Burhan ŞAHİN; Gülay TEMUÇİN (Turkish Journal of Gastroenterology, 2019)
-